2016
DOI: 10.1134/s1064229316060107
|View full text |Cite
|
Sign up to set email alerts
|

Chemodestructive fractionation of soil organic matter

Abstract: The method of chemodestructive fractionation is suggested to assess the composition of soil organic matter. This method is based on determination of the resilience of soil organic matter components and/or different parts of organic compounds to the impact of oxidizing agents. For this purpose, a series of solutions with similar concentration of the oxidant (K 2 Cr 2 O 7 ), but with linearly increasing oxidative capacity was prepared. Chemodestructive fractionation showed that the portion of easily oxidizable (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…It has been established that the content of humus in virgin soils corresponds to its average content: in gray forest soil it was 4.88%, in ordinary chernozem -4.34% (Figure 1 A study of the bichromate oxidizability of humus showed a certain predominance of the easily oxidizable fraction in the virgin gray forest soil (Figure 2 Moderately and hardly oxidizable forms in it are 25 and 30%, respectively, which indicates the presence of a balanced system of humic substances that is resistant to external influences [9,10]. The ordinary chernozem on the virgin lands turned out to be more enriched in easily oxidized forms of SOM (54%) compared to the gray forest soil, 33% are hardly oxidizable forms.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It has been established that the content of humus in virgin soils corresponds to its average content: in gray forest soil it was 4.88%, in ordinary chernozem -4.34% (Figure 1 A study of the bichromate oxidizability of humus showed a certain predominance of the easily oxidizable fraction in the virgin gray forest soil (Figure 2 Moderately and hardly oxidizable forms in it are 25 and 30%, respectively, which indicates the presence of a balanced system of humic substances that is resistant to external influences [9,10]. The ordinary chernozem on the virgin lands turned out to be more enriched in easily oxidized forms of SOM (54%) compared to the gray forest soil, 33% are hardly oxidizable forms.…”
Section: Resultsmentioning
confidence: 97%
“…Each fraction (part of oxidized SOM) is expressed as a percentage of the total carbon content of organic compounds (Ctot). To obtain results in differential form, the previous one was subtracted from each subsequent result (the amount of oxidized organic material) [9,10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the laboratory studies of all samples (organic and mineral), pH values were measured in the soil:water suspension (1:2.5) at static conditions using a pH meter ("Expert-pH", Saint Petersburg, Russia). In 29 samples from the mineral horizons, the content of total organic carbon was analyzed using a K 2 Cr 2 O 7 wet-combustion method [22]. Organic carbon stocks were calculated using the data on the carbon content, the thickness of the studied horizons, and their bulk density determined on the basis of the volumetric cylinder method.…”
Section: Laboratory Analysis and Data Treatmentmentioning
confidence: 99%
“…The latter separates different SOC fractions on the basis of resistance to oxidation or by the destruction of the mineral phase, solubility, and hydrolysability [19,20]. The boundary between labile and stable SOM in many studies is given by the resistance to oxidation [21] using K 2 Cr 2 O 7 as an oxidizing agent [22,23].…”
Section: Introductionmentioning
confidence: 99%